Treaty Interpretation: The Judicial Function between the Appreciation of States Parties and of Institutional Bodies - BONAFE', BEATRICE ILARIA (2014)
The dispute between Australia and Japan concerning the whaling in the Antarctic raised a number of issues of treaty interpretation. The article focuses in particular on the role that the unilateral position taken by the different actors involved in the conclusion or the implementation of a treaty can play in the interpretation of its provisions.